(untitled) (Heritage, 2024)
With the advent of artificial intelligence (AI) and advanced platforms such as ChatGPT, we are witnessing profound changes in the educational context that are increasingly becoming the focus of current scientific research and discourse. These technologies have the potential to completely redefine the future of education, introducing the possibility of personalized learning and the adaptation of teaching materials to the specific needs and abilities of each student. It also opens up the possibility of overcoming barriers in education in cases where there is no access to traditional education. However, in order to fully exploit the possibilities of these innovations, it is necessary to improve the level of technical literacy and develop the corresponding skills and competencies. Cultural contexts can significantly influence how students from different backgrounds understand and use AI systems. Existing biases in AI, stemming from predominantly Western-centric datasets, may indirectly promote stereotypes and lead to bias in learning outcomes. The use of artificial intelligence in education opens up a wide range of possibilities for improving the teaching process, but its application requires detailed analysis and consideration of ethical aspects, as well as issues of user security and privacy, as well as checking for bias that may be embedded in (AI) algorithms. A strategy that includes careful adoption and ethical use of artificial intelligence can bring significant progress in training and learning methods, and positively influence the development of educational standards and increase the quality of education. Only through informed and carefully monitored development, based on diversity, cultural sensitivity and equal global opportunities, is there hope for a true evolution of education with the help of new technologies.